Lathe machine optimum cutting speed for different materials - Ang, Liqi (2008)
In today's rapidly changing scenario in manufacturing industries, applications of optimization techniques in metal cutting processes was essential for a manufacturing unit to respond effectively to severe competitiveness and increasing demand of quality product in the market. Optimization methods in metal cutting processes, considered to be a vital tool for continual improvement of output quality in products [1]. This study focused in finding the optimum cutting speed that will produced the best surface finish for different materials. Lathe machine was used to conduct the experiment. Selecting the wrong cutting parameter may lead to several negative effects. For example: high maintenance cost of the Lathe machine, poor surface finish of the work pieces, short tool life, low production rate, material waste and increase production cost. In order to find out the optimum cutting speed for each material, there were other cutting parameters needed to be constant, such as feed rate, depth of cut and workpiece diameter. In machining operation, the quality of surface finish was an important requirement for many turned workpieces. Thus, the choice of optimized cutting parameters was very important for controlling the required surface quality. The focus of this study was to find a correlation between surface roughness and cutting speed.